Optical member and method for manufacturing optical member
Patent Information
- Application Number
- JP2023125307
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2025-02-14
AI Technical Summary
【0007】 本発明の実施形態によれば、偏光板の変色や脱色を抑制し、耐久性に優れた光学部材を提供することができる。
Smart Images

Figure 2025021538000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical member and a method for manufacturing an optical member. [Background technology]
[0002] In recent years, with the spread of thin displays, displays equipped with organic electroluminescence (EL) panels (organic EL display devices) have been proposed. Since organic EL panels have a highly reflective metal layer, they are prone to problems such as external light reflection and background glare. It is known that these problems can be prevented by providing a polarizing plate with a retardation layer, which is a combination of a polarizing plate and a retardation plate, on the viewing side of the organic EL panel body (for example, Patent Document 1 and Patent Document 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2002-372622 A [Patent Document 2] Patent No. 3325560 Summary of the Invention [Problem to be solved by the invention]
[0004] With the spread of thin displays, extremely high durability is sometimes required for organic EL panels, and also for polarizing plates. However, polarizing plates installed in organic EL display devices tend to easily discolor or lose color. This tendency can be remarkable when a transparent plate is installed on the viewing side for the purpose of protecting the display.
[0005] The present invention has been made to solve the above problems, and a main object of the present invention is to provide an optical member which is excellent in durability and which suppresses discoloration or decolorization of a polarizing plate. [Means for solving the problem]
[0006] 1. An optical member according to an embodiment of the present invention includes a polarizing plate having a polarizer having a first principal surface and a second principal surface opposing each other, and a first protective layer arranged on the first principal surface side of the polarizer, a transparent plate arranged on the first principal surface side of the polarizer, a retardation layer arranged on the second principal surface side of the polarizer, and a first pressure-sensitive adhesive layer arranged between the polarizing plate and the retardation layer and adjacent to the polarizing plate, wherein the moisture content of a laminated portion between the polarizing plate and the first pressure-sensitive adhesive layer is 3 g / m 2 The following is the result. 2. An organic EL panel according to an embodiment of the present invention includes the optical member according to 1 above, and an organic EL panel body. 3. A method for producing an optical member according to an embodiment of the present invention includes a polarizing plate having a polarizer having a first principal surface and a second principal surface opposed to each other, a first protective layer arranged on the first principal surface side of the polarizer, and a first pressure-sensitive adhesive layer arranged on the second principal surface side of the polarizer and adjacent to the polarizing plate, the method comprising the steps of: 2 The method includes preparing a laminate as follows, providing a transparent plate on the polarizing plate side of the laminate, and bonding a retardation layer to the first pressure-sensitive adhesive layer of the laminate. 4. A method for producing an optical member according to another embodiment of the present invention includes a polarizing plate having a polarizer having a first principal surface and a second principal surface opposed to each other, a first protective layer arranged on the first principal surface side of the polarizer, a first pressure-sensitive adhesive layer arranged adjacent to the polarizing plate, and a retardation layer arranged on the second principal surface side of the polarizer, in this order, and a moisture content of a laminated portion between the polarizing plate and the first pressure-sensitive adhesive layer is 3 g / m 2 The method includes preparing a laminate as follows; and providing a transparent plate on the polarizing plate side of the laminate. Effect of the Invention
[0007] According to an embodiment of the present invention, it is possible to provide an optical member having excellent durability by suppressing discoloration or decolorization of a polarizing plate. [Brief description of the drawings]
[0008] [Figure 1]1 is a schematic cross-sectional view showing a general configuration of an optical member according to one embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view illustrating an outline of an organic EL panel according to one embodiment of the present invention. [Figure 3A] 1 is a photograph showing the optical member of Comparative Example 1 before heating, as viewed from above. [Figure 3B] 1 is a photograph showing the optical member of Comparative Example 1 after heating, viewed from above. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, the embodiments of the present invention will be described with reference to the drawings, but the present invention is not limited to these embodiments. In order to clarify the description, the drawings may be schematic in terms of the width, thickness, shape, etc. of each part compared to the embodiment, but they are merely examples and do not limit the interpretation of the present invention. In addition, in the drawings, the same or equivalent elements are given the same reference numerals, and duplicate descriptions may be omitted.
[0010] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°.
[0011] [Optical components] FIG. 1 is a schematic cross-sectional view showing a general configuration of an optical member according to one embodiment of the present invention.
[0012] The optical member 100 includes a polarizing plate 30. The polarizing plate 30 includes a polarizer 10 having a first main surface 10a and a second main surface 10b facing each other, a first protective layer 21 arranged on the first main surface 10a side of the polarizer 10, and a second protective layer 22 arranged on the second main surface 10b side of the polarizer 10. The optical member 100 also includes a retardation layer 40 arranged on the second main surface 10b side of the polarizer 10, and a first adhesive layer 51 arranged between the polarizing plate 30 and the retardation layer 40. Unlike the illustrated example, the second protective layer 22 may be omitted. In this case, the retardation layer 40 can also function as a protective layer for the polarizer 10. The first adhesive layer 51 is arranged adjacent to the polarizing plate 30. Specifically, the first adhesive layer 51 is arranged adjacent to the second protective layer 22 or the polarizer 10.
[0013] Although not shown, the polarizing plate 30 may have an adhesive layer for bonding a protective layer to the polarizer 10. In the polarizing plate 30 shown in FIG. 1 , an adhesive layer may be provided between the polarizer 10 and the first protective layer 21, and an adhesive layer may be provided between the polarizer 10 and the second protective layer 22.
[0014] Although the illustrated retardation layer 40 is a single layer, the retardation layer 40 may have a laminated structure of two or more layers, unlike the illustrated example. For example, the retardation layer 40 may include two or more layers having different optical properties such as refractive index properties, in-plane retardation, Nz coefficient, and photoelastic coefficient.
[0015] The optical member 100 includes a transparent plate 60 disposed on the first main surface 10a side of the polarizer 10. The transparent plate 60 is attached to the polarizing plate 30 via a second pressure-sensitive adhesive layer 52. The optical member 100 is typically mounted on an organic EL panel. In the organic EL panel, the optical member 100 can be provided such that the transparent plate 60 is located closer to the viewing side than the polarizing plate 30.
[0016] A third adhesive layer 53 is provided on the surface of the retardation layer 40. The third adhesive layer 53 allows, for example, the optical member 100 to be attached to an organic EL panel body. Although not shown, in practice, a release liner is attached to the surface of the third adhesive layer 53, and the third adhesive layer 53 can be protected by the release liner. The release liner is temporarily attached to the third adhesive layer 53, for example, until the optical member 100 is used. Specifically, the release liner is temporarily attached to the third adhesive layer 53 until the optical member 100 is mounted on the organic EL panel. As the release liner, a plastic film having a surface coated with a release agent is typically used.
[0017] In the optical member 100, the moisture content of the laminated portion between the polarizing plate 30 and the first pressure-sensitive adhesive layer 51 is, for example, 3 g / m 2 or less, preferably 2.5 g / m 2 More preferably, it is 2 g / m or less. 2 or less, more preferably 1.5 g / m 2 or less, and particularly preferably 1 g / m 2 or less, most preferably 0.5 g / m 2 The following is the result.
[0018] In one embodiment, in manufacturing the optical member 100, a laminate including the polarizing plate 30 and the first adhesive layer 51 is formed in advance. For example, the optical member 100 can be obtained by laminating the polarizing plate 30 and the first adhesive layer 51 in advance to form a laminate, adjusting the moisture content of the laminated portion between the polarizing plate 30 and the first adhesive layer 51, bonding the retardation layer 40 to the laminate, and providing a transparent plate 60. For example, the optical member 100 can be obtained by laminating the polarizing plate 30, the first adhesive layer 51, and the retardation layer 40 in advance to form a laminate, adjusting the moisture content of the laminated portion between the polarizing plate 30 and the first adhesive layer 51, and providing a transparent plate 60 to the laminate. The adjustment of the moisture content can be typically achieved by placing the laminate in any appropriate environment. For example, the moisture content is adjusted by placing the laminate in a heated environment of 105°C or higher (heating to 105°C or higher). Furthermore, for example, the moisture content is adjusted by placing the laminate in an environment with a temperature of 23° C. to 25° C. and a relative humidity of 52% to 55%.
[0019] <Polarizer> The polarizer is typically a film containing a dichroic material (typically, iodine).
[0020] The polarizer preferably exhibits absorptive dichroism at any wavelength of 380 nm to 780 nm. The crossed transmittance (Tc) of the polarizer is preferably 0.5% or less, more preferably 0.1% or less, and even more preferably 0.05% or less. The single transmittance (Ts) of the polarizer is, for example, 41.0% to 45.0%, and preferably 42.0% or more. The polarization degree (P) of the absorptive polarizing film is, for example, 97.0% to 99.997%, preferably 99.0% or more, more preferably 99.5% or more, and even more preferably 99.9% or more.
[0021] The thickness of the polarizer is not particularly limited, but is, for example, 1 μm or more and 50 μm or less. It is preferably 40 μm or less, more preferably 30 μm or less, further preferably 20 μm or less, and may be 10 μm or less. By using a polarizer with such a thickness, the above moisture content can be satisfactorily achieved. On the other hand, the thickness of the polarizer is preferably 2 μm or more, more preferably 3 μm or more.
[0022] The crossed transmittance, single transmittance and degree of polarization can be measured, for example, using an ultraviolet-visible spectrophotometer. The degree of polarization P can be calculated from the obtained Tp and Tc by measuring the single transmittance Ts, parallel transmittance Tp and crossed transmittance Tc using an ultraviolet-visible spectrophotometer, using the following formula. Note that Ts, Tp and Tc are Y values measured using a 2-degree visual field (C light source) according to JIS Z 8701 and corrected for visibility. Polarization degree P(%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100
[0023] The polarizer may be produced by any appropriate method. Specifically, the polarizer may be produced from a single-layer resin film or may be produced using a laminate of two or more layers.
[0024] A method for producing a polarizer from the above-mentioned single-layer resin film typically includes subjecting the resin film to a dyeing treatment with a dichroic substance such as iodine or a dichroic dye, and a stretching treatment. As the resin film, for example, a hydrophilic polymer film such as a polyvinyl alcohol (PVA) film, a partially formalized PVA film, or an ethylene-vinyl acetate copolymer partially saponified film is used. The method may further include an insolubilization treatment, a swelling treatment, a crosslinking treatment, etc. Such a production method is well known and commonly used in the art, so a detailed description thereof will be omitted.
[0025] The polarizer obtained by using the laminate can be produced, for example, by using a laminate of a resin substrate and a resin film or resin layer (typically, a PVA-based resin layer). Specifically, the laminate can be produced by applying a PVA-based resin solution to a resin substrate, drying the resin substrate to form a PVA-based resin layer on the resin substrate, and obtaining a laminate of the resin substrate and the PVA-based resin layer; and stretching and dyeing the laminate to make the PVA-based resin layer into a polarizer. In this embodiment, preferably, a PVA-based resin layer containing a halide and a PVA-based resin is formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution and stretching it. Furthermore, the stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95°C or higher) before stretching in the aqueous boric acid solution. In addition, in this embodiment, preferably, the laminate is subjected to a drying shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction. Typically, the manufacturing method of the present embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, even when PVA is applied onto a thermoplastic resin, it is possible to increase the crystallinity of PVA, and high optical properties can be achieved. In addition, by simultaneously increasing the orientation of PVA in advance, problems such as a decrease in the orientation of PVA and dissolution can be prevented when immersed in water in the subsequent dyeing and stretching steps, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the orientation disorder and the decrease in the orientation of the PVA molecules can be suppressed compared to when the PVA-based resin layer does not contain a halide, and high optical properties can be achieved. Furthermore, by shrinking the laminate in the width direction by the drying shrinkage treatment, high optical properties can be achieved. A polarizing plate can be obtained by laminating a protective layer on the peeled surface obtained by peeling the resin substrate from the obtained resin substrate / polarizer laminate, or on the surface opposite to the peeled surface. Details of such a method for producing a polarizer are described in, for example, JP 2012-73580 A and Japanese Patent No. 6470455. The entire disclosures of these publications are incorporated herein by reference.
[0026] The polarizer may contain boric acid. From the viewpoint of durability, the boric acid content of the polarizer is preferably 5% by weight or more, more preferably 10% by weight or more. If the boric acid content is less than 5% by weight, for example, the polarizer may be polyenized, and durability may decrease. On the other hand, the boric acid content of the polarizer is preferably 25% by weight or less. The boric acid content of the polarizer can be adjusted, for example, by adjusting the boric acid content in the aqueous solution used in the manufacturing process of the polarizer. The boric acid content can be calculated, for example, from the neutralization method using the following formula as the amount of boric acid contained in the polarizer per unit weight.
number
[0027] The iodine content of the polarizer is preferably 2% by weight or more. If the iodine content of the polarizer is within this range, for example, due to a synergistic effect with the boric acid, curling that may occur during heating is suppressed, and the polarizer can have excellent durability. On the other hand, the iodine content of the polarizer is preferably 10% by weight or less. The iodine content of the polarizer means the total amount of iodine contained in the polarizer. Specifically, in the polarizer, iodine is present in the form of iodine ions (I-), iodine molecules (I 2 ), polyiodide ion (I 3 - , I 5 - The amount of iodine in the aqueous solution may be calculated by, for example, a calibration curve method for X-ray fluorescence analysis.
[0028] The polyiodine ion exists, for example, in the form of an iodine complex with PVA in a polarizer. The formation of such a complex can cause absorption dichroism in the visible light wavelength range. Specifically, a complex of PVA and triiodide ion (PVA·I 3 - ) may have an absorption peak around 470 nm, and the complex of PVA and pentaiodide ion (PVA·I 5 -) may have an absorption peak around 600 nm. As a result, polyiodide ions may absorb light in a wide range of visible light depending on their form. - ) may have an absorption peak at about 230 nm and is not substantially involved in the absorption of visible light. Therefore, polyiodide ions present in the form of an iodine complex with PVA may be mainly involved in the absorption performance of the polarizer.
[0029] <Protective layer> The protective layers may be made of any suitable film that can be used as a protective layer for a polarizer. Examples of materials that are the main components of the films that make up the protective layers include cellulose-based resins such as triacetyl cellulose (TAC), polyester-based, polyvinyl alcohol-based, polycarbonate-based, polyamide-based, polyimide-based, polyethersulfone-based, polysulfone-based, polystyrene-based, cycloolefin-based such as polynorbornene, polyolefin-based, (meth)acrylic, acetate-based, and other resins. Here, (meth)acrylic refers to acrylic and / or methacrylic.
[0030] The first protective layer may be subjected to surface treatment such as hard coat treatment, anti-reflection treatment, anti-sticking treatment, anti-glare treatment, etc., as necessary. Specifically, the first protective layer may be composed of a laminate film having the above-mentioned film as a substrate and a surface treatment layer formed on the substrate. The thickness of the surface treatment layer is preferably 0.5 μm to 10 μm, more preferably 1 μm to 7 μm, and further preferably 2 μm to 5 μm.
[0031] The thickness of the first protective layer can be appropriately set. The thickness of the first protective layer is preferably 10 μm to 80 μm, more preferably 15 μm to 70 μm, and further preferably 20 μm to 50 μm. Note that, when the protective layer is surface-treated, the thickness of the first protective layer includes the thickness of the surface treatment layer.
[0032] The second protective layer is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm, and the retardation Rth(550) in the thickness direction is -10 nm to +10 nm. The thickness of the second protective layer is preferably 10 μm to 80 μm, more preferably 20 μm to 70 μm, and further preferably 30 μm to 50 μm.
[0033] In one embodiment, the moisture permeability of the first protective layer is preferably higher than that of the second protective layer. The moisture permeability can be determined, for example, by the cup method (JIS Z 0208). The moisture permeability can be measured, for example, in an environment at a temperature of 40° C. and a relative humidity of 92%.
[0034] <Adhesive layer> The form of the adhesive constituting the adhesive layer is not particularly limited, and for example, a water-based adhesive, a solvent-based adhesive, a hot melt adhesive, an active energy ray curing adhesive, etc. are used. Among these, for example, a water-based adhesive or an active energy ray curing adhesive is preferably used because it can reduce the thickness of the adhesive layer. The thickness of the adhesive layer is preferably 0.01 μm to 5 μm, more preferably 0.03 μm to 3 μm.
[0035] <Retardation layer> The retardation layer may be a single layer as shown in the figure, or may have a laminated structure of two or more layers. When the retardation layer is a single layer, the retardation layer can typically function as a λ / 4 plate. The retardation layer is typically provided to impart antireflection characteristics to the organic EL display device. The retardation layer typically exhibits a refractive index characteristic of nx > ny = nz. The in-plane retardation Re(550) of the retardation layer is preferably 100 nm to 190 nm, more preferably 110 nm to 170 nm, and even more preferably 120 nm to 160 nm. Here, "ny = nz" includes not only the case where ny and nz are exactly equal, but also the case where they are substantially equal. Specifically, ny > nz or ny < nz may occur. The Nz coefficient of the retardation layer is preferably 0.9 to 1.5, more preferably 0.9 to 1.3. By satisfying such a relationship, an organic EL display device having a very excellent reflection hue can be obtained.
[0036] When the retardation layer is a single layer, the retardation layer preferably exhibits an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light. In this case, Re(450) / Re(550) of the retardation layer is preferably 0.8 or more and less than 1, more preferably 0.8 or more and 0.95 or less. With such a configuration, very excellent antireflection characteristics can be realized.
[0037] The angle formed by the slow axis of the retardation layer and the absorption axis of the polarizer is preferably 40° to 50°, more preferably 42° to 48°, and even more preferably about 45°. If the angle is within such a range, by using the retardation layer as a λ / 4 plate as described above, an organic EL display device having very excellent antireflection characteristics can be obtained.
[0038] The retardation layer may be made of any appropriate material as long as it satisfies the above-mentioned characteristics. Specifically, the retardation layer may be a resin film (including a stretched resin film) or may be an alignment and solidification layer of a liquid crystal compound. Preferably, the retardation layer is made of a resin film. In this case, the thickness of the retardation layer is, for example, 10 μm to 100 μm, preferably 10 μm or more and 70 μm or less, and more preferably 20 μm or more and 60 μm or less.
[0039] Examples of the resin contained in the resin film include polycarbonate-based resins, polyester carbonate-based resins, polyester-based resins, polyvinyl acetal-based resins, polyarylate-based resins, cyclic olefin-based resins, cellulose-based resins, polyvinyl alcohol-based resins, polyamide-based resins, polyimide-based resins, polyether-based resins, polystyrene-based resins, and acrylic-based resins. These resins may be used alone or in combination. Examples of the combination method include blending and copolymerization. When the λ / 4 member exhibits reverse dispersion wavelength characteristics, a resin film containing a polycarbonate-based resin or a polyester carbonate-based resin (hereinafter, sometimes simply referred to as a polycarbonate-based resin) can be suitably used.
[0040] Any suitable polycarbonate-based resin can be used as the polycarbonate-based resin. For example, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from at least one dihydroxy compound selected from the group consisting of alicyclic diol, alicyclic dimethanol, di-, tri- or polyethylene glycol, and alkylene glycol or spiro glycol. Preferably, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, a structural unit derived from an alicyclic dimethanol and / or a structural unit derived from a di-, tri- or polyethylene glycol; more preferably, it contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from a di-, tri- or polyethylene glycol. The polycarbonate-based resin may contain a structural unit derived from another dihydroxy compound as necessary. Details of polycarbonate-based resins that can be suitably used for λ / 4 components and methods for forming λ / 4 components are described, for example, in JP 2014-10291 A, JP 2014-26266 A, JP 2015-212816 A, JP 2015-212817 A, and JP 2015-212818 A, and the descriptions in these publications are incorporated herein by reference.
[0041] <Adhesive layer> The pressure-sensitive adhesive layers may each be set to any appropriate thickness. For example, the thickness of first pressure-sensitive adhesive layer 51 and third pressure-sensitive adhesive layer 53 is preferably 1 μm to 30 μm, more preferably 3 μm to 20 μm. The thickness of second pressure-sensitive adhesive layer 52 is, for example, 20 μm to 500 μm, more preferably 100 μm to 300 μm.
[0042] The adhesive layer may be made of any suitable adhesive. As a specific example, the adhesive layer may be made of an adhesive having an acrylic polymer, a silicone polymer, a polyester, a polyurethane, a polyamide, a polyether, a fluorine-based polymer, a rubber-based polymer, or the like as a base polymer. By adjusting the type, number, combination, and compounding ratio of the monomers constituting the base polymer of the adhesive, as well as the compounding amount of the crosslinking agent, the reaction temperature, the reaction time, and the like, an adhesive having desired properties according to the purpose can be prepared. The base polymer of the adhesive may be used alone or in combination of two or more kinds. An acrylic polymer is preferably used as the base polymer. Specifically, the adhesive layer is preferably made of an acrylic adhesive.
[0043] <Transparent plate> The transparent plate has an appropriate mechanical strength. For example, a transparent resin plate such as an acrylic resin or a polycarbonate resin, or a glass plate is used. The thickness of the transparent plate is, for example, 0.5 mm to 5 mm.
[0044] [Organic EL panel] The optical member can be used in an organic EL display device, and an organic EL display device according to an embodiment of the present invention includes the optical member. Fig. 2 is a schematic cross-sectional view showing an outline of an organic EL panel according to one embodiment of the present invention. Specifically, it is a schematic cross-sectional view showing an outline of an organic EL panel included in an organic EL display device according to one embodiment of the present invention.
[0045] The organic EL panel 200 includes an optical member 100 and an organic EL panel body 70. In the organic EL panel 200, the optical member 100 is attached to the organic EL panel body 70 by a third adhesive layer 53.
[0046] The illustrated organic EL panel body 70 has a substrate 71 and an upper structure layer 72 including a circuit layer including thin film transistors (TFTs) and the like, an organic light emitting diode (OLED), a sealing film for sealing the OLED, and the like. For example, when a flexible substrate (e.g., a resin substrate) is used as the substrate 71, the obtained organic EL display device can be curved, bent, folded, rolled up, and the like. The upper structure layer 72 includes, for example, a nitrogen-containing layer (e.g., a nitride layer such as silicon nitride or silicon oxynitride), and ammonia (including ammonium ions) can be generated from the upper structure layer 72.
[0047] When the polarizing plate 30 is exposed to a high temperature environment while moisture is present in the polarizing plate 30, ammonia (substantially, ammonium ions) is likely to be generated from the upper structure layer 72 of the organic EL panel main body 70, and the ammonia that has entered the polarizing plate 30 (polarizer 10) decomposes the dichroic material (typically, iodine complex) contained in the polarizer 10, causing discoloration or decoloration. If the transparent plate 60 is provided, moisture is likely to be trapped in the polarizing plate 30, and moisture is likely to flow into the organic EL panel main body 70, causing the generation of gas such as ammonia, and discoloration or decoloration of the polarizing plate 30 (polarizer 10) is likely to occur. As described above, since the moisture content is adjusted in the optical member 100, discoloration or decoloration of the polarizing plate 30 (polarizer 10) can be suppressed even when the transparent plate 60 is provided, and durability can be excellent. Furthermore, the problem of discoloration or decoloration of the polarizing plate can be solved without changing the design of the organic EL panel main body 70. EXAMPLES
[0048] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. The thickness, retardation value, and water content are values measured by the following measurement methods. Furthermore, unless otherwise specified, "parts" and "%" are based on weight. <Thickness> The thickness of 10 μm or less was measured using a scanning electron microscope (manufactured by JEOL, product name "JSM-7100F"), and the thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu, product name "KC-351C"). <Phase difference value> The phase difference value at each wavelength at 23°C was measured using a Mueller matrix polarimeter (Axometrics, product name "Axoscan"). <Moisture content> After measuring the initial weight of a sample cut to a size of 50 mm x 150 mm from the member (laminate) to be measured, the sample was dried by heating at 105°C for 15 hours, and the weight immediately after drying was measured. The weight after drying was then subtracted from the initial weight to obtain the moisture content per unit area (g / mm 2 The weight was measured in an environment with a temperature of 23°C and a relative humidity of 55%.
[0049] [Example 1] (Preparation of polarizer) A long roll of polyvinyl alcohol (PVA) resin film (manufactured by Kuraray, "PE4500") having a thickness of 45 μm was uniaxially stretched in the longitudinal direction to 5.9 times its original size using a roll stretching machine, while simultaneously undergoing swelling treatment, dyeing treatment, crosslinking treatment, and washing treatment in this order, and then dried at 70°C for 5 minutes to produce a polarizer having a thickness of 18 μm. In the swelling treatment, the film was stretched 2.2 times while being treated with pure water at 20°C. In the dyeing treatment, the iodine concentration was adjusted so that the single transmittance of the obtained polarizer was 43.4%, and the film was stretched 1.4 times while being treated in an aqueous solution at 30°C in which the weight ratio of iodine to potassium iodide was 1:7. The crosslinking treatment was a two-stage crosslinking treatment, and in the first stage, the film was stretched 1.2 times while being treated in an aqueous solution at 40°C in which boric acid and potassium iodide were dissolved. The aqueous solution in the first stage crosslinking treatment had a boric acid content of 5.0 wt% and a potassium iodide content of 3.0 wt%. In the second stage crosslinking treatment, the film was stretched 1.6 times while being treated in an aqueous solution at 65°C in which boric acid and potassium iodide were dissolved. The aqueous solution in the second stage crosslinking treatment had a boric acid content of 4.3 wt% and a potassium iodide content of 5.0 wt%. In the above cleaning treatment, the treatment was performed with an aqueous potassium iodide solution at 20° C. The potassium iodide content of the aqueous solution used in the cleaning treatment was 2.6% by weight.
[0050] (Preparation of polarizing plate) A 28 μm thick HC-TAC film was attached to one surface (first main surface) of the polarizer via an ultraviolet-curing adhesive. Specifically, the adhesive was applied to a thickness of 1.0 μm, and the two films were attached using a rolling machine. Thereafter, the adhesive was cured by irradiating the HC-TAC film with ultraviolet rays from the HC-TAC film side. The HC-TAC film was a film in which a 3 μm thick hard coat (HC) layer was formed on a 25 μm thick triacetyl cellulose (TAC) film, and the TAC film was attached to the polarizer side. Next, an acrylic film having a lactone ring structure and a thickness of 20 μm was attached to the other surface (second main surface) of the polarizer via a UV-curable adhesive. Specifically, the adhesive was applied to a thickness of 1.0 μm, and the films were attached using a rolling machine. After that, the adhesive was cured by irradiating the acrylic film with UV rays. In this way, a polarizing plate was obtained.
[0051] (Preparation of Acrylic Pressure-Sensitive Adhesive Composition) A monomer mixture containing 99 parts by weight of butyl acrylate and 1 part by weight of 4-hydroxyethyl acrylate was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Furthermore, 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was charged together with 100 parts by weight of ethyl acetate for 100 parts by weight of this monomer mixture, and nitrogen gas was introduced while gently stirring to replace the atmosphere in the flask with nitrogen. The liquid temperature in the flask was kept at 55°C and a polymerization reaction was carried out for 8 hours to prepare a solution of an acrylic polymer with a weight average molecular weight (Mw) of 1.8 million. An acrylic pressure-sensitive adhesive composition was prepared by blending 0.02 parts by weight of an isocyanate crosslinking agent (trimethylolpropane / xylylene diisocyanate adduct, manufactured by Tosoh Corporation, "Takenate D110N") and 0.2 parts by weight of a silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., "X-41-1056") with 100 parts by weight of the solid content of the obtained acrylic polymer solution.
[0052] (Preparation of first adhesive layer) The above acrylic adhesive composition was applied to a release liner (polyethylene terephthalate film treated with a silicone-based release agent, thickness 38 μm, manufactured by Mitsubishi Chemical Polyester Film Corporation, "MRF38") so that the adhesive layer would have a thickness of 20 μm after drying, and was dried at 90°C for 1 minute to form a first adhesive layer on the release liner.
[0053] (Preparation of polarizing plate with adhesive layer) The first pressure-sensitive adhesive layer was attached to the acrylic film side of the obtained polarizing plate, the release liner was peeled off from the first pressure-sensitive adhesive layer, and the plate was left in this state for 24 hours under an environment of a temperature of 23°C and a relative humidity of 55%, to obtain a pressure-sensitive adhesive layer-attached polarizing plate. The moisture content of the obtained pressure-sensitive adhesive layer-attached polarizing plate was 2.5 g / m 2 It was.
[0054] (Preparation of retardation film) Polymerization was carried out using a batch polymerization apparatus consisting of two vertical reactors equipped with stirring blades and a reflux condenser controlled at 100° C. Bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane 29.60 parts by mass (0.046 mol), isosorbide (ISB) 29.21 parts by mass (0.200 mol), spiroglycol (SPG) 42.28 parts by mass (0.139 mol), diphenyl carbonate (DPC) 63.77 parts by mass (0.298 mol), and calcium acetate monohydrate 1.19×10 as a catalyst. -2 Part of mass (6.78×10 -5 mol) was charged. After the inside of the reactor was purged with nitrogen under reduced pressure, heating was performed with a heat medium, and stirring was started when the inside temperature reached 100 ° C. 40 minutes after the start of the temperature increase, the inside temperature was reached 220 ° C., and while controlling to maintain this temperature, the pressure was reduced and 90 minutes after reaching 220 ° C., the pressure was reduced to 13.3 kPa. Phenol vapor by-produced with the polymerization reaction was led to a reflux condenser at 100 ° C., a small amount of monomer components contained in the phenol vapor were returned to the reactor, and the uncondensed phenol vapor was led to a condenser at 45 ° C. and recovered. Nitrogen was introduced into the first reactor to restore the pressure to atmospheric pressure, and the oligomerized reaction liquid in the first reactor was transferred to the second reactor. Next, the temperature increase and pressure reduction in the second reactor were started, and the inside temperature was set to 240 ° C. and the pressure to 0.2 kPa in 50 minutes. Thereafter, polymerization was allowed to proceed until the specified stirring power was reached. When the predetermined power was reached, nitrogen was introduced into the reactor to restore pressure, and the produced polyester carbonate resin was extruded into water and the strands were cut to obtain pellets.
[0055] The obtained polyester carbonate resin (pellets) was vacuum-dried at 80°C for 5 hours, and then a long resin film having a thickness of 135μm was produced using a film-forming device equipped with a single-screw extruder (manufactured by Toshiba Machine Co., Ltd., cylinder setting temperature: 250°C), a T-die (width 200mm, setting temperature: 250°C), a chill roll (setting temperature: 120-130°C) and a winder. The obtained long resin film was stretched in the width direction at a stretching temperature of 143°C and a stretching ratio of 2.8 times to obtain a retardation film having a thickness of 48μm. The Re(550) of the obtained retardation film was 143nm, Re(450) / Re(550) was 0.86, and the Nz coefficient was 1.12.
[0056] (Production of optical components) The retardation film was attached to the first pressure-sensitive adhesive layer side of the pressure-sensitive adhesive layer-attached polarizing plate. A slide glass (manufactured by Matsunami Glass Industry Co., Ltd., product name "S200423") was prepared as a transparent plate. Then, the polarizing plate side of the above-mentioned polarizing plate with an adhesive layer was attached to the prepared transparent plate via an adhesive having a thickness of 250 μm. In this manner, an optical member was produced.
[0057] [Example 2] In the preparation of the polarizing plate with the adhesive layer, the plate was placed in a heating environment at 90°C for 2 hours, and the moisture content of the polarizing plate with the adhesive layer was reduced to 0.2 g / m 2 An optical member was produced in the same manner as in Example 1, except for the above.
[0058] [Comparative Example 1] In the preparation of the polarizing plate with the adhesive layer, the plate was placed in an environment of 40°C and 92% relative humidity for 5 hours, and the moisture content of the polarizing plate with the adhesive layer was reduced to 6.7 g / m 2 An optical member was produced in the same manner as in Example 1, except for the above.
[0059] The following evaluations were carried out for the Examples and Comparative Examples. The evaluation results are summarized in Table 1. <Evaluation> The obtained optical component (size: 50 mm × 150 mm) was attached to an alkali-free glass plate having a 500 nm-thick silicon oxynitride film formed on its surface via an adhesive layer formed as described below, and then heated for 75 hours at 95°C, a temperature required for in-vehicle displays, etc. The cross transmittance Tc of the optical member before and after heating was measured using an ultraviolet-visible spectrophotometer (Otsuka Electronics Co., Ltd., "LPF-2000"), and the cross transmittance change ΔTc (ΔTc=Tc after heating−Tc before heating) was calculated. The reflectance of the optical member before and after heating was measured using a spectrophotometer (Konica Minolta's "CM-2600d") The measurement was performed with a reflector (Toray Advanced Film Co., Ltd., product name "Cerapeel DMS-X42") placed on the back side of the glass, and the change in reflectance (reflectance after heating - reflectance before heating) was calculated. The cross transmittance Tc and reflectance were measured at the center of the optical member.
[0060] (Formation of adhesive layer) A monomer mixture containing 94.9 parts by weight of butyl acrylate, 5 parts by weight of acrylic acid, and 0.1 parts by weight of 2-hydroxyethyl acrylate was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Furthermore, 0.3 parts by weight of dibenzoyl peroxide as a polymerization initiator was charged together with ethyl acetate for 100 parts by weight of this monomer mixture, and nitrogen gas was introduced while gently stirring to replace the atmosphere in the flask with nitrogen. The liquid temperature in the flask was kept at 60°C and a polymerization reaction was carried out for 7 hours. Next, ethyl acetate was added to the resulting reaction liquid to adjust the solid concentration to 30% by weight, and a solution of an acrylic polymer with a weight average molecular weight (Mw) of 2.2 million was prepared. An acrylic adhesive was prepared by blending 100 parts by weight of the solid content of the obtained acrylic polymer solution with 0.6 parts by weight of a trimethylolpropane / tolylene diisocyanate adduct (product name: Coronate L, manufactured by Tosoh Corporation) and 0.075 parts by weight of a silane coupling agent (product name: KBM403, manufactured by Shin-Etsu Chemical Co., Ltd.). The obtained acrylic adhesive was applied to the release liner so that the adhesive layer would have a thickness of 20 μm after drying, and dried at 90° C. for 1 minute to form an adhesive layer on the release liner.
[0061] [Table 1]
[0062] Fig. 3A is a photograph of the optical member of Comparative Example 1 before heating in the above evaluation, as viewed from above, and Fig. 3B is a photograph of the optical member of Comparative Example 1 after heating in the above evaluation, as viewed from above. As shown in Figs. 3A and 3B, the optical member of Comparative Example 1 discolored (turned red) due to heating.
[0063] The present invention is not limited to the above-described embodiment, and various modifications are possible. For example, the above-described embodiment may be replaced with a configuration that is substantially the same as the configuration shown in the above-described embodiment, a configuration that provides the same effect, or a configuration that can achieve the same purpose. [Industrial Applicability]
[0064] The optical member according to the embodiment of the present invention is suitable for use in, for example, an organic EL panel and an organic EL display device. [Explanation of symbols]
[0065] 10 Polarizer 21 First protective layer 22 Second protective layer 30 Polarizing plate 40 Retardation layer 51 First adhesive layer 52 Second adhesive layer 53 Third adhesive layer 60 Transparent plate 70 Organic EL panel body 100 Optical components 200 OLED panel
Claims
1. a polarizing plate including a polarizer having a first principal surface and a second principal surface facing each other, and a first protective layer disposed on the first principal surface side of the polarizer; A transparent plate disposed on a first main surface side of the polarizer; A retardation layer disposed on a second principal surface side of the polarizer; A first pressure-sensitive adhesive layer is disposed between the polarizing plate and the retardation layer and adjacent to the polarizing plate, The moisture content of the laminated portion between the polarizing plate and the first pressure-sensitive adhesive layer is 3 g / m 2 Below is the Optical components.
2. An organic EL panel comprising the optical member according to claim 1 and an organic EL panel body.
3. a polarizing plate having a polarizer having a first principal surface and a second principal surface opposed to each other, and a first protective layer disposed on the first principal surface side of the polarizer; and a first pressure-sensitive adhesive layer disposed on the second principal surface side of the polarizer and disposed adjacent to the polarizing plate, 2 Providing a laminate of: providing a transparent plate on the polarizing plate side of the laminate; and bonding a retardation layer to the first pressure-sensitive adhesive layer of the laminate. A method for manufacturing an optical member.
4. a polarizing plate having a polarizer having a first principal surface and a second principal surface opposed to each other, a first protective layer disposed on the first principal surface side of the polarizer, a first pressure-sensitive adhesive layer disposed adjacent to the polarizing plate, and a retardation layer disposed on the second principal surface side of the polarizer, in this order; 2 Providing a laminate of: and providing a transparent plate on the polarizing plate side of the laminate. A method for manufacturing an optical member.
Citation Information
Patent Citations
Composite optical retardation plate, circularly polarizing plate and liquid crystal display, organic el display device
JP2002372622A
Retardation film and optical device using the same
JP3325560B2